Developing Bockie; The Evolution of Vegan Bockwurst for the Indonesian Market - joe, ivan; marie, shiftra; bartels, marta; putra, aditya nova; nurfitriana, siti; listyorini, niken taufiqurrahmi (IULI Publisher, 2024)
The emergence of plant-based foods has sparked a global shift towards sustainable and healthier dietary choices. This paper explores the development and introduction of a novel vegan sausage into the Indonesian market. Utilizing locally sourced tofu as the primary ingredient, this sausage aims to cater to the growing demand for plant-based alternatives while addressing sustainability concerns within the food industry. Incorporating a taste enhancer from the Korean company, Cheil Jedang Food & Nutrition Technology (CJ FNT), which initiated this endeavor as a competitive challenge, enhances the flavor profile of the sausage, making it appealing to a wide range of consumers. Through a combination of market analysis, nutritional evaluation, and sensory testing, this paper examines the feasibility and potential impact of introducing such a product in Indonesia. By highlighting the benefits of plant-based diets for both personal health and environmental sustainability, this study contributes to the promotion of sustainable food practices in emerging markets Keywords: plant based food, sausage, sustainability, food industry